Determinant of mobile devices acceptance for learning among students in developing country - Shittu, Ahmed Tajudeen; Madarsha, Kamal Basha; Michael, Fakomogbon O.; Mukhtar, Alhaji Liman (Universiti Malaya, 2013)
This study was conducted to understand the determinant of mobile devices for learning among students in developing world. A sample of 247 undergraduate students from Malaysia and Nigeria were involved in the study. An adapted but modified survey instrument was used to gather the data of the study. The variable of the study are perceived usefulness, perceived ease of use, perceived enjoyment, facilitating condition, behavioral intention and student attitude are the independent variable of the study. T-test and Multiple regression analysis was conducted. The findings of the study shows that there is no significant difference in acceptance to use mobile device for learning among science and non-science students but there is significant difference in acceptance to use mobile device for learning among male and female students. Perceived usefulness, perceived enjoyment, facilitating condition, and behavioral intention were found to significantly influence students’ acceptance of Mobile Device for learning, surprisingly perceived ease of use and student attitude was statistically insignificant in determining student acceptance to use MD for learning.